Jonas Harrison papers - Harrison, Jonas, 1777-1836.
Carbon copies of typewritten transcripts of business and personal letters in a letterbook kept by Harrison while collector of customs and internal revenue. Chief correspondent is Samuel Harrison Smith.
Transcribed by Samuel E. Asbury from microfilm of the original letterbook held in the Buffalo and Erie County Historical Society.
U.S. customs and tax collector residing in Geneseo County, N.Y., who later emigrated to Shelby County, Tex., where he practiced law.
Collection material in English.
Inventory available with the collection.
Keywords: Smith, Samuel Harrison, -- 1772-1845 -- Correspondence; Customs administration -- New York (State); Tax collection -- New York (State); Geneseo County (N.Y.) -- History; Public officials